Hunt club [videorecording (DVD)] - Suvari, Mena, 1979-; Stojan, Maya, 1986-; Van Dien, Casper, 1968-; Rourke, Mickey (Uncork'd Entertainment, 2023)
A gripping story of male hunters who lure women to their island with the chance to win $100K in a hunt, only to discover that they are the hunted. But this time they have messed with the wrong girls and discover women can be better hunters than men.